2015
DOI: 10.1002/hed.24051
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of human papillomavirus status with apparent diffusion coefficient of diffusion‐weighted MRI in head and neck squamous cell carcinomas

Abstract: In HNSCC, positive HPV status correlates with low mean apparent diffusion coefficient. The favorable prognostic value of low pretreatment apparent diffusion coefficient might be partially attributed to patients with a positive HPV status. © 2015 Wiley Periodicals, Inc. Head Neck 38: E613-E618, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 24 publications
4
37
1
Order By: Relevance
“…A recent study used ADC as a marker to compare the mean pretreatment ADC values between HPV + (n = 6) and HPV‐ (n = 67) HNSCC and found that HPV + HNSCC showed significantly lower ADC compared with HPV‐ 32. In HNSCC, cellular tumors with lower pre‐TX ADC values have shown a more favorable outcome to chemo‐radiation therapy than necrotic tumors with higher pre‐TX ADC values 12, 33…”
Section: Discussionmentioning
confidence: 99%
“…A recent study used ADC as a marker to compare the mean pretreatment ADC values between HPV + (n = 6) and HPV‐ (n = 67) HNSCC and found that HPV + HNSCC showed significantly lower ADC compared with HPV‐ 32. In HNSCC, cellular tumors with lower pre‐TX ADC values have shown a more favorable outcome to chemo‐radiation therapy than necrotic tumors with higher pre‐TX ADC values 12, 33…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] It has been postulated that poor outcomes of some squamous cell carcinomas are due to tumor factors that are known to increase ADC values, such as micronecrosis, lower cellularity, and, more recently, negative human papillomavirus status and high stromal content. 3,[20][21] Of note, the ratio of stroma to tumor cells is recognized as an important determinant of outcome in head and neck squamous cell carcinoma. In regard to NPC, research now also shows that stroma-rich NPCs are associated with poor prognosis and an increased risk of relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Recent publications have attempted to determine whether mean ADC values calculated by monoexponential fitting could be used to determine the HPV status in HNSCC. 12,14,22 In contrast to the intravoxel incoherent motion biexponential model, the monoexponential model does not differentiate between molecular movement caused by microperfusion and true diffusion caused by Brownian movement. 23 To obtain a robust fitting, biexponential models require the acquisition of 6 -12 b-values, leading to increased examination time and a higher percentage of motion artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…Publications evaluating the association between mean ADC values with monoexponential fitting and the HPV status in HNSCC have yielded contradictory results; although some authors suggested that mean ADCs at 1.5T are lower in HPVϩ than in HPVϪ HNSCCs, others found no significant differences. 12,14,22 In these studies, the methodology of ROI contouring, the type of DWI sequence used, and the range and num- ber of b-values vary. Nakahira et al 12 contoured the largest axial cross-sectional tumor area on a single section without excluding necrotic portions, Driessen et al 22 contoured the entire tumor volume excluding necrotic portions, and Schouten et al 14 contoured the largest cross-sectional area on a single section excluding necrotic portions.…”
Section: Discussionmentioning
confidence: 99%